Inovasi Layanan Pijat Bayi Berbasis Homecare sebagai Upaya Peningkatan Kesehatan Bayi - Fitri Fitri; Arfiani Arfiani; Nadya Auliya Ramadani; Mutiara Sabrina; Niken Stevani (Lembaga Pengembangan Kinerja Dosen, 2026)
Infant massage is an early stimulation method that plays a role in increasing infant weight gain, sleep quality, and comfort. However, limited parental resources and access to healthcare facilities prevent massage services from being optimally implemented. This community service activity aims to improve infant health through homecare-based infant massage services that are easily accessible to families. The activity was conducted on June 22, 2025, in Bulukumba Regency, targeting five infants aged 2–5 months. The activity methods included: (1) initial weight measurement, (2) education on correct massage techniques, (3) massage using olive oil for 15–20 minutes, and (4) monitoring infant sleep patterns and comfort. Repeat measurements were conducted after the intervention. Results showed post-intervention weight gain in all infants, improved sleep patterns (infants fell asleep more easily and slept longer), and increased appetite. Mothers also demonstrated improved self-massage skills. In conclusion, homecare-based infant massage has been proven effective in improving infant comfort, sleep patterns, and weight gain. This program is worthy of continuation and expansion to support community midwifery services